Recent Advances in AIEgens for Metal Ion Biosensing and Bioimaging - Li, Yongming (Molecules, 2019)
Metal ions play important roles in biological system. Approaches capable of selective and sensitive detection of metal ions in living biosystems provide in situ information and have attracted remarkable research attentions. Among these, fluorescence probes with aggregation-induced emission (AIE) behavior offer unique properties. A variety of AIE fluorogens (AIEgens) have been developed in the past decades for tracing metal ions. This review highlights recent advances (since 2015) in AIE-based sensors for detecting metal ions in biological systems. Major concerns will be devoted to the design principles, sensing performance, and bioimaging applications.